Impact of the originating martensitic phase on the character of martensitic phase transformation - Svetec, Milan (Anali PAZU, 2023)
In the article, we discuss the influence of the locally perturbed order parameter in austenitic-martensitic phase transformation on the character of the phase transformation. We choose Landau type mean field approximation which covers the most important features of the proposed theoretical description.
Keywords: approximation; austenitic-martensitic phase transformation; avstenitno-martenzitni fazni prehod; Ginzburg term; Ginzburgov člen; Landau mean field; Landau-ovo povprečno polje; modeliranje; parameter